Bortezomib sensitizes multiple myeloma to NK cells via ER-stress-induced suppression of HLA-E and upregulation of DR5. (1st February 2019) - Carlsten, Mattias; Namazi, Ali; Reger, Robert; Levy, Emily; Berg, Maria; St. Hilaire, Cynthia; Childs, Richard W.
ABSTRACT: Although the proteasome inhibitor bortezomib has significantly improved the survival of patients with multiple myeloma (MM), the disease remains fatal as most patients eventually develop progressive disease. Recent data indicate that MM cells can evade bortezomib-induced cell death by undergoing autophagy as a consequence of endoplasmatic reticulum (ER)-stress induced by proteasome inhibition. Here we show that bortezomib sensitizes MM cells to NK cell killing via two distinct mechanisms: a) upregulation of the TRAIL death receptor DR5 on the surface of MM cells and b) ER-stress induced reduction of cell surface HLA-E. The latter mechanism is completely novel and was found to be exclusively controlled by the inhibitory receptor NKG2A, with NKG2A single-positive (NKG2A SP ) NK cells developing a selective augmentation in tumor killing as a consequence of bortezomib-induced loss of HLA-E on the non-apoptotic MM cells. In contrast, the expression of classical HLA class I molecules remained unchanged following bortezomib exposure, diminishing the augmentation of MM killing by NK cells expressing KIR. Further, we found that feeder cell-based ex vivo expansion of NK cells increased both NK cell TRAIL surface expression and the percentage of NKG2A SP NK cells compared to unexpanded controls, substantially augmenting their capacity to kill bortezomib-treated MM cells. Based on these findings, we hypothesize that infusion of ex vivo expanded NK cells following treatment with bortezomib could eradicate MM cells that would normally evade killing through proteasome inhibition alone, potentially improving long-term survival among MM patients.